A (re)construção do Direito Processual Previdenciário: um estudo para a adequada compreensão da coisa julgada em matéria previdenciária - Schuster, Diego Henrique (Universidade do Vale do Rio dos Sinos, 2025)
This doctoral thesis analyzes the importance of studying the institution of res judicata, taking as a backdrop social security law, where it acquires unique features and is often difficult to approach, especially within classical doctrine – which is bound by civil law postulates. To this end, we first seek to establish the conditions for the formation of res judicata, with particular attention to the notion of legal certainty. Thus, the main hypothesis is constructed: the work aims to analyze the scope of material res judicata. Therefore, the premise guiding the systematization of the topic is to “put everything in its place”, defining the objective, temporal, and subjective limits of res judicata – and this is what ordinary civil procedure prescribes. On the other hand, res judicata can (must) be relativized based on an understanding of criteria already established in law (as in res judicata secundum eventum probationis, present in class actions), and not based on arguments of justice – a claim to morally correct the law. At this point, therefore, the plan is to offer a legal response to the unacceptable situation of denying social protection to those who need it and are entitled to it, but who, for a variety of reasons, were unable to prove the fact constituting their right in the first lawsuit. The general objective of this paper is to study the institution of res judicata, seeking answers to the different situations involving its application (or not). The specific objectives are: to study the importance of due process as a right guarantee in the formation of res judicata; to investigate the relationship between the challenge to the Professional Social Security Profile as a prejudicial issue, taking as a starting point (or return) art. 503, §§ 1º and 2º, of the CPC; to study what constitutes (or does not constitute) res judicata, that is, within the objective, temporal, and subjective limits of res judicata, with special attention to the role of the cause of action; to propose a broader and more up-to-date jurisprudential research to the present day, in order to problematize the different situations involving the application (or not) of res judicata; to propose a broader case law study up to the present day; to examine the different situations involving res judicata, that is, what constitutes (or does not constitute) res judicata, within its subjective, objective, and temporal limits; to study the different instruments – some limited –capable of relativizing the force of res judicata in the Brazilian legal system; to analyze the problem of the lack of exhaustive cognition and, consequently, the (in)aptitude for the formation of res judicata; to present the peculiarities of social security disputes in order to justify differentiated treatment in procedural terms, which takes as its starting point the study of repetitive appeal REsp 1.352.721/SP (Topic 629), in order to question the future of res judicata secundum eventum probationis; investigate the historical horizon, including after the judgment of the precedent; seek in the rescissory action solutions for the violation of the adversarial principle and the mistaken application of res judicata; and problematize the concept of “new evidence” based on a holistic and integrated analysis of the law as a whole. The research thus demonstrates the need to seek legally controllable/reliable criteria to enable the development of legal solutions, aiming to realize fundamental social rights and protect the insured.
Keywords: Processo Previdenciário; Coisa julgada; Segurança jurídica; Social Security Procedure; Res judicata; Legal certainty; ACCNPQ::Ciências Sociais Aplicadas::Direito